RESENHA NEUWIRTH, Rostam J. Law in the Time of Oxymora. A Synaesthesia of Language, Logic and Law. Londres: Routledge, 2018. - Ferreira, Mariana Colucci Goulart Martins (Juris Poiesis - Qualis A3, 2019)
NEUWIRTH, Rostam J. Law in the Time of Oxymora. A Synaesthesia of Language, Logic and Law. Londres: Routledge, 2018.